DYSTOCIA DUE TO CONJOINED TWIN MONSTER IN A COW - JAYAKUMAR, C; AZEEZ, ABDUL; PROMOD, K; PANICKER, SNEHA (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to a conjoined twin monster in a 4 ½ year old crossbred cow with normal gestation and prolonged labour was reported. Obstetrical examination revealed a ’Dicephalic, distomus, tetraopthalmus, dibrachius, quadrapus and dicaudatus’ monster. Cesarean section was resorted to deliver the dead monster. The anatomical structure of a rare case of conjoined twin monster is described and discussed.